ANALISIS FAKTOR PENYEBAB WASTE PADA PROYEK PEMBANGUNAN JALAN TOL BALIKPAPAN-SAMARINDA - Fitria Arwina Munawaroh; Oryza Lhara Sari (Universitas Lambung Mangkurat, 2022)
In the implementation of construction projects, one of the problems that often occurs is inefficiency and waste. According to the Lean Construction Institute, in construction projects there is a lot of waste in the form of activities that use resources but do not add value (non-value adding). Project waste will become a problem and can increase project costs if not immediately anticipated. By eliminating waste in non-value-added activities and applying lean tools to essential value-added and non-value-added activities. In this toll road construction project, there is a problem in the form of delays in the construction process caused by several factors, one of which is related to land acquisition. Therefore, it is necessary to analyze the factors causing waste in the Balikpapan - Samarinda Toll Road Development Project. This research aims to find out the waste variables and the factors that cause the most frequent waste in the project. The method used in this research is Borda method. Borda method is used to rank the most frequent variables and factors. The result shows that the most frequent waste variable in Balikpapan - Samarinda Toll Road Construction Project is waiting time which has a weight of 0.187. Meanwhile, the factor causing the most frequent waste in the Balikpapan - Samarinda Toll Road Development Project is due to unfavorable weather which has a weight of 0.074.